2020
DOI: 10.1186/s13073-020-00789-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signature in IgE-mediated food allergies

Abstract: Background Multiple studies suggest a key role for gut microbiota in IgE-mediated food allergy (FA) development, but to date, none has studied it in the persistent state. Methods To characterize the gut microbiota composition and short-chain fatty acid (SCFAs) profiles associated with major food allergy groups, we recruited 233 patients with FA including milk (N = 66), sesame (N = 38), peanut (N = 71), and tree nuts (N = 58), and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 51 publications
(58 reference statements)
6
57
0
1
Order By: Relevance
“…SCFAs promote the growth of beneficial intraluminal bacteria and homeostasis through the maintenance of an intact gastrointestinal barrier. [35,40,73] Additionally, they have been shown to exert anti-inflammatory effects in animal models, as they support the expansion of Treg cells and upregulate the production of interleukin (IL)-10 by increasing the expression of transcription factor FOXP3 (Forkhead box protein 3) via inhibition of histone deacetylation (Figure 3). [40,73,74] Several authors observed lower levels of acetate, propionate, butyrate, valerate, isobutyrate, and isovalerate in feces of allergic children, [35,73] or children who will develop IgE-FA (>1 year old), [40] while Thompson-Chagoyan et al (2011) showed higher concentrations of fecal butyrate and BSCFA in children with IgE-FA (< 1 year old).…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…SCFAs promote the growth of beneficial intraluminal bacteria and homeostasis through the maintenance of an intact gastrointestinal barrier. [35,40,73] Additionally, they have been shown to exert anti-inflammatory effects in animal models, as they support the expansion of Treg cells and upregulate the production of interleukin (IL)-10 by increasing the expression of transcription factor FOXP3 (Forkhead box protein 3) via inhibition of histone deacetylation (Figure 3). [40,73,74] Several authors observed lower levels of acetate, propionate, butyrate, valerate, isobutyrate, and isovalerate in feces of allergic children, [35,73] or children who will develop IgE-FA (>1 year old), [40] while Thompson-Chagoyan et al (2011) showed higher concentrations of fecal butyrate and BSCFA in children with IgE-FA (< 1 year old).…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…In addition, there is evidence that the dysbiosis of the GI microbiota prior to FA subsequently impacts the progression of FA. An investigation by Goldberg et al (2020) discovered that babies with food allergies showed a lower abundance of Prevotella copri than babies without food allergies, with the concomitant increase in SCFAs, which may destroy intestinal homeostasis and barrier function. Currently, microbiota-directed therapy has been a new focus for the treatment of food allergies, and studies with larger sample sizes are needed to clarify the specific effects ( Schuijs et al, 2015 ).…”
Section: The Gastrointestinal Microbiota and Allergic Diseasesmentioning
confidence: 99%
“…Clearly this is an important and promising area of research. Interestingly, eosinophilic esophagitis is associated with IgE-mediated food allergies which is associated with enteric microbiome alterations in non-ASD children [90,91]. As microbiome imbalances have been associated with ASD [92] and may have important consequences in immune regulation [93], microbiome alterations may be playing a role in immune dysregulation in ASD.…”
Section: Discussionmentioning
confidence: 99%